PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN EKOWISATA DI HUTAN PINUS ROMBENG: IMPLIKASI UNTUK KEBERLANJUTAN EKONOMI LOKAL - Sukran; Farid Said; Darwis; Sabran Laori; Sri Wahyuni (Wonderful-Journal of Tourism Destination, 2026)
This study aims to formulate a community-based ecotourism development strategy at Rombeng Pine Forest, Bonto Lojong Village, Bantaeng Regency, using a qualitative approach and SWOT analysis method. Data were collected through interviews with managers, local communities, and tourists, as well as field observations. The results indicate that the ecotourism quality in this area is still limited, especially regarding infrastructure and supporting facilities. This study proposes an amenity development model that involves community empowerment through skill training and the enhancement of sustainable tourism facilities. The impact of this model is expected to improve the quality of the tourist experience and provide more stable income for the local community. Additionally, the study emphasizes the importance of sustainable ecotourism management, involving various stakeholders in planning and implementation. The implications of this research highlight the importance of developing policies that support community-based ecotourism and raising awareness of environmental conservation. This research also contributes to the development of knowledge in the field of ecotourism and offers recommendations for ecotourism managers in similar areas